(untitled) (Eurasian Scientific Herald, 2024)
Russia’s economy has progressively moved from a planned to a mixed, marketoriented economy. It possesses vast natural resource reserves, especially in relation to Russian oil and gas reserves, and as a result, its exports have substantial economic strength. According to the IMF, it ranked sixth in terms of purchasing power parity (PPP) in 2023, the World Bank ranked fifth, and nominal GDP ranked it as the eleventh largest economy in the world. The high fluctuations in Russia’s GDP assessed in US dollars can be attributed to a fluctuating currency exchange rate. In 2012, Russia became the final large economy to join the World Trade Organization (WTO). Indeed, in some research it is been shown that there are a lot of factors that effect on the development of the Russia economy and one the most important of them is GDP (Gross Domestic Product). The major goal of this study is to identify the challenges that the Russia will encounter and how they will affect the growth of the US economy over the next five years. Secondary data from secondary sources were retrieved for the current investigation such as an independent variable and a dependent variable used in this study, the data were prepared from the Federal Reserve Economic data (FRED), from 1990 to 2022. In our research used annual time-series data and the OLS model on GDP was the dependent variable, while Consumer Price Index, Unemployment, Export to Import ratio, Producer price Index were the independent variables.